2009
DOI: 10.1167/iovs.09-3515
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger Function of Resident Autofluorescent Perivascular Macrophages and Their Contribution to the Maintenance of the Blood–Retinal Barrier

Abstract: All these morphologic and functional features are consistent with those described for brain Mato cells. Thus, this study showed the presence of autofluorescent perivascular macrophages, different from microglia, with a scavenger function that may contribute to the maintenance of the blood-retinal barrier in healthy conditions and that are also involved in retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 26 publications
2
62
1
1
Order By: Relevance
“…In our study, apoptotic RGCs were observed in 20-week-old db/db mice, consistent with the reduced PERG amplitudes. Moreover, the number of apoptotic cells was increasing with age, accompanied with evident induction of IBA-1 and F4/80 expression, both of which were considered as established marker for microglia/macrophages in the retina [48]. Additionally, IBA-1 and F4/80 positive cells as well as apoptosis cells were also found in the INL, which was implied to be affected by db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, apoptotic RGCs were observed in 20-week-old db/db mice, consistent with the reduced PERG amplitudes. Moreover, the number of apoptotic cells was increasing with age, accompanied with evident induction of IBA-1 and F4/80 expression, both of which were considered as established marker for microglia/macrophages in the retina [48]. Additionally, IBA-1 and F4/80 positive cells as well as apoptosis cells were also found in the INL, which was implied to be affected by db/db mice.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the area postrema, a circumventricular organ devoid of BBB, PVM restrict the entry of tracers larger than 10 kDa [45]. In addition, in the mouse retina, PVM move along retinal blood vessels and accumulate blood-borne molecules without disruption of the blood-retina barrier [46]. In experimental and human retinopathy, in which the barrier is disrupted, PVM migrate to the lesion site and may play a role in limiting the leakage of blood components into the retina [46].…”
Section: Pathophysiological Role Of Perivascular Macrophagesmentioning
confidence: 99%
“…Several Scara5 positive cells were found within the outer nuclear layer (Figure 8C). The immunolabeling with anti-2F8 antibody, a macrophage marker [44], revealed the presence of 2F8 positive cells also within the outer nuclear layer, suggesting that the Scara5 positive cells observed may correspond to 2F8 positive macrophages that migrated to lesion sites [27].…”
Section: Resultsmentioning
confidence: 90%
“…We received human eye samples without knowledge of the donor's identity, only biological data, such as sex and age, were available. Results obtained from the same human retinas were previously published [27], [28].…”
Section: Methodsmentioning
confidence: 89%